Author guidelines for book chapters from Global Thinking Center (Centro de Pensamiento Global – CEPEG) (2020)
The Global Thinking Center (Centro de Pensamiento Global – CEPEG), from Universidad Cooperativa de Colombia, provides in this document the minimal guidelines that authors must take into account when interested in publishing manuscripts within the books belonging to the Acontecer Mundial, Pensamiento Global and Grupo de reflexión sobre integración y desarrollo en América Latina y Europa (Gridale) Collections.